Increased lipid peroxidation and erythrocyte glutathione peroxidase activity of patients with type 2 diabetes mellitus: Implications for obesity and central obesity. (September 2019) - Gunawardena, H.P.; Silva, K.D.R.R.; Sivakanesan, R.; Katulanda, P.
Abstract: Aim: Both diabetes and obesity are a proxidant state by increased generation of reactive oxygen species. Obesity and central obesity is common among most of patient with type 2 diabetes. We aimed to assess the effect of obesity on GPx and SOD activity and lipid peroxidation of patients with type 2 diabetes mellitus, prediabetes and normoglycaemic healthy controls. Methods: Hundred and forty seven type 2 diabetic patients (T2D), forty seven prediabetics (PDM) and hundred and six normoglycaemic controls (NGC) were recruited. T2D, PDM and NGC individuals were further clustered on the presence of obesity and central obesity. Erythrocyte GPx and SOD were determined using enzymatic reagent kits. Lipid peroxidation marker, malondialdehyde (MDA) was measured using thiobarbituric acid reactive substances (TBARS) assay. Results: T2D had higher GPx activity and plasma MDA compared to PDM and NGC. PDM showed higher SOD activity than T2D and NGC. Obese and centrally obese T2D had higher GPx activity and plasma MDA with markedly reduced SOD activity. Conclusion: Obesity and central obesity has further triggered the oxidative stress in T2D as indicated by higher plasma MDA and lower SOD activity. However, rise of GPx activity in parallel to the MDA among obese and centrally obese T2D suggest the induction of "reductive stress".